2013
DOI: 10.1136/archdischild-2012-302500
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity among child travellers with sickle-cell disease visiting tropical areas: an observational study in a French tertiary care centre

Abstract: Travels to tropical areas are associated with high morbidity in children with SCD. Salmonella infection is a particularly significant threat, and empirical antibiotic therapy should be prescribed routinely for traveller's diarrhoea in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 7 publications
2
12
0
Order By: Relevance
“…The hospitalisation and consultation rates for exacerbations in children with CHDs during the month after travel were higher than those during the month before travel. The difference was not significant, probably because of the small number of patients and events, but our results are in accordance with those of a previous study in which the hospitalisation rates of children with SCD increased after travel 6. The risk of exacerbations after returning from travel is still poorly discussed during pretravel consultations.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The hospitalisation and consultation rates for exacerbations in children with CHDs during the month after travel were higher than those during the month before travel. The difference was not significant, probably because of the small number of patients and events, but our results are in accordance with those of a previous study in which the hospitalisation rates of children with SCD increased after travel 6. The risk of exacerbations after returning from travel is still poorly discussed during pretravel consultations.…”
Section: Discussionsupporting
confidence: 88%
“…Among the children with SCD, the hospitalisation rate during the period following the return was 17%. Previous studies have reported similar rates: between 9.6% and 30.7% 6 7. One child with a CHD died during travel, the child had recently received a genetic diagnosis of atypical HUS and had never had any manifestations of the disease before the trip.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…These include disorders of oxidative cellular killing, such as chronic granulomatous disease, in which nontyphoidal Salmonella is described as the most common cause of bloodstream infection and the third leading cause of all infections (151). Children who are homozygous for sickle cell disease are susceptible to invasive nontyphoidal Salmonella infections (152). In addition, inherited deficiencies of cytokines that are known to be critical for intracellular killing, particularly interleukin-12 (IL-12) and IL-23, are associated with invasive nontyphoidal Salmonella (153).…”
Section: Nontyphoidal Salmonellamentioning
confidence: 99%
“…These include chronic granulomatous disease (a defect of oxidative cellular killing [35], and inherited deficiencies of cytokines that are known to be critical for intracellular killing, particularly IL12 and IL23. Children homozygous for sickle cell disease are also extremely susceptible to iNTS infections [36,37], while heterozygosity for the sickle cell gene is protective against invasive Gram negative infections, including iNTS disease, most likely through a protective effect against malaria [38].…”
Section: Invasive Non-typhoidal Salmonella (Ints) Diseasementioning
confidence: 99%